Causal explanation of academic enthusiasm based on the interaction of teachers and English language learners: Self-regulation, academic hope, and academic engagement among English language learners - Izadpanah, Siros; Rezaei, Yasaman Mohammad (Frontiers in Psychology, 2022)
Introduction The present research investigates the causal explanation of academic enthusiasm based on the interaction between teachers and English learners: self-regulation, academic hope, and academic engagement among English language learners. Methods The implementation method of this descriptive research and research design was structural equation correlation. The research’s statistical population included intermediate Zanjan city learners (50,977 people) who were studying in the academic year 2021-2022. This research used multi-stage cluster random sampling to test the proposed model. The following questionnaires were used to collect data: Academic enthusiasm (Fredericks et al.); Teacher-student interaction questionnaire (Moray and Zurich); Academic hope questionnaire (Khormai and Kameri); Self-Regulation Questionnaire (Bouffard) and academic engagement (Zarang). Lisrel software was used for data analysis and evaluation of the proposed model using structural equation modeling. Results The results of the present study showed that teacher-student interaction, academic self-regulation, academic engagement, and academic hope are related to students’ academic enthusiasm. The results of the present study also support the role of mediators of academic self-regulation, academic engagement, and academic hope in the causal relationships between teacher-student interaction and academic enthusiasm. Discussion: Based on this, it can be concluded that with the improvement of teacher-student interaction, the level of academic self-regulation, academic engagement, and academic hope of students increases, and these factors together increase their academic enthusiasm. Therefore, it is suggested that to increase academic engagement, academic self-regulation, and academic hope in the students in the education system, attention should be paid to the position of the students’ academic enthusiasm.